2012
DOI: 10.1007/s00217-012-1664-4
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characteristics and thermal inhibition kinetics of polyphenol oxidase extracted from Thompson seedless grape

Abstract: Polyphenol oxidase (PPO) was isolated from Thompson seedless grape (Vitis vinifera 'Thompson Seedless'), and its biochemical characteristics were studied. The PPO showed activity to catechol and D, L-DOPA, but not towards monophenol L-Tyrosine, diphenols guaiacol and caffeic acid, and triphenols pyrogallic acid and gallic acid. Apparent Michaelis-Menten constant (K m ) and maximum velocity of the reaction (V max ) values were 45.0 ± 0.05 mM and 500.0 ± 15.3 OD 400 nm /min for catechol, and 34.6 ± 0.03 mM and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
(67 reference statements)
0
16
2
Order By: Relevance
“…This is qualitatively similar to the results obtained with strawberries (Dalmadi et al 2006). By using the Lineweaver-Burk plot, the Food Sci., 33, 2015 (2) (Zheng et al 2012). The data indicated that the loquat cv.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This is qualitatively similar to the results obtained with strawberries (Dalmadi et al 2006). By using the Lineweaver-Burk plot, the Food Sci., 33, 2015 (2) (Zheng et al 2012). The data indicated that the loquat cv.…”
Section: Resultsmentioning
confidence: 94%
“…First, some inhibitors such as citric acid and oxalic acid chelate metallic ions, copper ions for PPO and ferric ions for POD (Sun et al 2012). Second, some compounds compete with the substrates and combine so that fewer amounts of the substrates are catalysed, such as l-cysteine (Zheng et al 2012). Third, reducing agents, such as ascorbic acid, reduce the block enzymatic browning by interacting with o-quinone and other substances (Gómez-López 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Persimmon PPO keep along the time more than 60% of its activity at 60 and 70°C (Navarro et al, ). Other reported thermal inactivation PPO temperatures are jackfruit (90°C, <5 min) (Tao et al, ), blueberry (80°C, <2 min) (Terefe, Delon, Buckow, & Versteeg, ), Thompson seedless grape (70°C, <10 min) (Zheng, Shi, & Pan, ), Bramley's seedling apple (70°C, 15 min) (Ni Eidhin et al, ), Butter lettuce (70°C, 50 min) (Gawlik‐Dziki et al, ), and litchi (60°C, 10 min) (Mizobutsi et al, ).…”
Section: Resultsmentioning
confidence: 98%
“…Cell integrity and cell membranes might be damaged during drying, depending on the drying method and pretreatments (Lewicki, 1998;Ahmad et al, 2006), and therefore polyphenols in the plant undergoing drying could be oxidised by polyphenol oxidase (PPO). The optimum temperature of grape PPO differs among grape varieties and ranges from 25 o C to 45 o C (Zheng et al, 2012;Ünal & Şener, 2014). The temperature of the sun-drying method is close to optimum temperature of grape PPO.…”
Section: Anthocyanins and Phenolic Compoundsmentioning
confidence: 99%